Synchronous multi-species alternations between the northern Humboldt and Kuroshio Current systems. (January 2019) - Oozeki, Yoshioki; Ñiquen Carranza, Miguel; Takasuka, Akinori; Ayón Dejo, Patricia; Kuroda, Hiroshi; Tam Malagas, Jorge; Okunishi, Takeshi; Vásquez Espinoza, Luis; Gutiérrez Aguilar, Dimitri; Okamura, Hiroshi; Guevara Carrasco, Renato
Abstract: Synchrony of species alternations in the northern Humboldt (NHCS) and Kuroshio (KCS) Current systems was examined by comparing time series data of landings and population statistics of major small pelagic fish species along with climate indices from 1960 to 2015. Target species were anchovy Engraulis ringens, sardine Sardinops sagax, jack mackerel Trachurus murphyi and chub mackerel Scomber japonicus in the NHCS, and anchovy E. japonicus, sardine S. melanostictus, jack mackerel T. japonicus and chub mackerel in the KCS. The time series of total biomass and spawning stock biomass (SSB) of anchovy and sardine for the NHCS and the KCS were well correlated, as were the landings data. Landings of small pelagic fish including jack mackerel and chub mackerel indicated that multi-species alternations may also be synchronous at a community level between the two current systems. Peak landings of jack mackerel and chub mackerel were observed between peaks of anchovy and sardine in both current systems, although the relationships between jack mackerel and chub mackerel differed between the current systems. The species alternations between anchovy and sardine are most reasonably attributable to environmentally-induced changes in the biomass as a major mechanism, although the effect of fishing activity cannot be excluded. Future studies will be required to compare biological characteristics of multiple small pelagic fish species in the pelagic food chain in each current system.